ASKING QUESTION METHOD IN L1 FOR ENGLISH LEARNERS: DOES IT FACILITATE COMPREHENSION? - Meriyati, Meriyati; Usadiati, Wahyuningsih; Karani, Elanneri (Journal Compound: Improving the Quality of English Education, 2020)
Asking question method in L1 is a promising method in improving students’ speaking in English. This study adopted descriptive qualitative design with the subjects of 31 students of grade X at SMK Negeri 1 Raren Batuah, Central Kalimantan. The main data were obtained from the results of students’ test scores of speaking about procedure text, and the supporting data were taken from the result of questionnaire. The research finding shows a considerable increase in English speaking when the students were asked questions of AQM using L1 that enhanced comprehension.